(untitled) (Journal of Environmental Science and Natural Resources, 2021)
An agro-climatic study was conducted at different areas (Bhatiapara, Kashiar Char and Morichar Char) of Mymensingh district with 25 years of climatic data (i.e., temperature, humidity and rainfall) to observe the climatic variability and their impact on the productivity of three types of crops such as Boro, Jute and Wheat. Production of all the three crops were found as increasing. In Boro season, the production increased by 0.057 ton per hectare per year. Jute production increased by 0.029 ton per hectare and Wheat production increased by 0.067 ton per hectare in each year, respectively. Humidity has influence on seasonal Boro production whereas temperature and rainfall didn’t influence the production. Temperature has influences on both Jute and Wheat production. From correlation analysis, it was revealed that average humidity has considerable influence on seasonal Boro production than all other crops. However, most of the time the production showed increasing trend with some exceptions. The study recommends that local adaptation practices should be scrutinized, the role of institutional support should be highlighted and national adaptation strategies and resilience should be strengthened. Environ. Sci. & Natural Resources, 12(1&2): 51-55, 2019